Methods and protocols for secure key negotiation using IKE. - Borella, M.S (IEEE Network : the magazine of global information exchange)
The IETF has advanced the IPsec protocols to draft standard status. These protocols include mechanisms for the establishment of a secure channel, via cryptographic key exchange, over an insecure medium. Such a channel can then be used for ensuring the confidentiality, authentication, and/or integrity of the communications between two parties. We explain the algorithms and protocols of IPsec's Internet Key Exchange (IKE) and discuss the types of security that the various IKE modes provide